Inhibition of bacillus spores germination by cinnamon bark, fingerroot, and moringa leaves extract - Sri Agung Fitri Kusuma; Rendy Septyadi; Ferry Ferdiansyah Sofian (Wolters Kluwer Medknow Publications, 2022)
This study was intended to discover the natural food preservatives by comparing the antibacterial effect of the ethanolic extract of cinnamon bark, finger root, and moringa leaves toward Bacillus cereus both the vegetative cells and spores. The antibacterial activities of the investigated extracts were assessed against cells using the agar diffusion method. Whereas the sporicidal test was performed by observing the colony growth, after various times of incubation (1, 3, and 5 h). The investigated extracts produced inhibition in a diameter ranging from 10.6 to 35.3 mm, and it can be classified that the extract of cinnamon bark was the most potent extract to inhibit the vegetative cells form, followed by fingerroot and the moringa leaves extract. Consistently, the ethanolic extract of cinnamon bark and fingerroot significantly yielded sporicidal activities higher than the moringa leaves extract. Both extracts exerted sporicidal activity within 1 h of contact time at the lowest test concentration of 5% w/v, whereas moringa leaves extract required a longer contact time (5 h) at higher concentration of 20% w/v. It can be concluded that cinnamon bark and fingerroot extract have great potential as effective food preservative candidates to inhibit the B. cereus growth than moringa leaves extract.